Climate Change ECHO: Telementoring to Improve Climate Literacy for Health Professionals - Joanna G. Katzman, MD, MSPH; David Herring, MS; Stefan Wheat, MD; Ralph J. Groves, MD; Briana Kazhe-Dominguez, BS; Chamron Martin; Kent Norsworthy, MA; Jinyang Liu, MA; Sabrina Lord, MHA; Laura E. Tomedi, PhD, MPH (Elsevier, 2023)
Introduction: Climate change is a global public health crisis. Most clinicians and public health professionals do not receive adequate education to manage and communicate climate-related health impacts to their patients. Methods: From July 2021 to February 2022, the Project ECHO Climate Change and Human Health program completed 22 weekly trainings for health professionals. These virtual telementoring sessions were designed to improve both knowledge and self-efficacy about climate-related health impacts and climate change‒related communication skills. Results: Between July 2021 and February 2022, a total of 804 unique participants (from 44 states and 25 countries) attended the sessions. Participants were nurses (24.7%), physicians (16.8%), and public health professionals (8.5%). They completed weekly Zoom polls measuring their knowledge and self-efficacy. On average, participants strongly agreed or agreed that they had learned skills taught in each session (average percentage of those who strongly agreed or agreed=94.6%, range=66.7%-100.0%). Participants (31%) also completed a weekly postsession survey. A total of 91% rated the sessions as excellent or very good regarding evidenced-basis, and 89% rated sessions as excellent or very good regarding improved communication skills with patients and colleagues. Conclusions: Given the global climate crisis, the Climate Change and Human Health ECHO is successfully building resources and capacity for clinicians and public health professionals.